PENGEMBANGAN CASE BASED REASONING (CBR) PADA APLIKASI RESEP JAJAN PASAR BERBASIS WEB MOBILE (Information Technology and Telematics, 2014)
AbstractThis study proposes an approach to the snack food market is the Case-Based Reasoning approach (CBR).CBR process through four stages: Retrieve, Reuse, revise and Retain. It is most important in determining the value of CBR similarity or similarity between the cases stored in the case base with new cases that will be addressed. The advantage with this method is the application of knowledge builders do not have to do directly with the acquisition of knowledge of an expert.The system will provide the output of the type of snack market which will be known resemblance input material with material menu (Process retrive). In the process of doing the weighting system using the Nearest Neighbour method.Keywords:Development System, Case-Based Reasoning, Recipes Snack Market, Mobile Web